What is going to change in EU rural development policies after 2013? Main implications in different national contexts - Francesco Mantino (Bio-based and Applied Economics, 2013)
This paper will address the changes the CAP post‐2013 may bring to its second pillar in EU countries. After the presentation of the legislative package put forward by the European Commission, a debate emerged in some countries on how to define rural development strategies for the period 2014‐2020. The paper will discuss positive innovations and main challenges of the new rural development policies with respect to what happened in the 2007‐2013 period. In particular, the paper intends to focus on the following issues: 1) which relevant changes have been introduced in the rural development framework; 2) how these changes can influence the preparation of the next programming period 2014-2020, looking more in depth at three countries (Italy, Spain and France); 3) what lessons can be drawn from this reform and the initial implementation in three countries in terms of institutional changes and their likely success and failure. This analysis concludes that the success or failure of the 2014-2020 reform of rural development will significantly depend on what types of transaction costs and incentive systems will be brought about within the programming system. These two factors in turn will strongly depend on the way the different actors will perceive the different costs and incentives, their expectations on the role of rural development programmes in a context where budget for agriculture is shrinking everywhere, and finally their capability to build new strategic alliances and cooperation at every level (national, regional and local) with other economic and social actors. Future policy scenarios might bring new and heavy constraints to rural development policies and consequently might also reduce the opportunities of institutional innovations.